E-commerce in India Economic and legal perspectives - Gupta, Pralok (ed) (New Delhi Sage, 2020)
E -commerce is growing at an exponential rate in India. Despite this, it is still at an evolving stage as economic and regulatory frameworks pertaining to various segments of e-commerce are being put into place by the government. This book presents a comprehensive analysis of the economic and regulatory aspects of the e-commerce sector by assessing the trends and characteristics, and addressing the issues and challenges associated with it. It dwells into key issues including FDA regulations, taxation, valuation of e-commerce companies, market structure, competition, payment mechanism, Blockchain and currencies, and logistics. The issues and challenges addressed in this book frequently appear as discussion points in policy debates, research forums and popular media. However, information on these is scant and often scattered. This book bridges gaps in the available literature on e-commerce.
Keywords: E-commerce